SNARE proteins contribute to calcium cooperativity of synaptic transmission - Stewart, Bryan A. (The National Academy of Sciences, 2000)
A hallmark of calcium-triggered synaptic transmission is the cooperative relationship between calcium and the amount of transmitter released. This relationship is thought to be important for improving the efficiency of synaptic vesicle exocytosis. Although it is generally held that cooperativity arises from the interaction of multiple calcium ions with a single calcium-sensing molecule, the precise molecular basis of this phenomenon is not known. The SNARE proteins are known to be critical for synaptic vesicle exocytosis. We therefore tested for a contribution of SNARE proteins to cooperativity by genetically reducing the levels of syntaxin IA and neuronal-synaptobrevin in Drosophila. Surprisingly, we found that reducing these SNARE proteins also reduced Ca(2+) cooperativity. Thus, SNARE proteins are important for determining the cooperative relationship between calcium and synaptic transmission.